A Liberal before Liberalism: Karl Hermann Scheidler and the New Hegelians. (September 2021) - Barbour, Charles
Abstract : This paper is the first substantial investigation in English or German of the work and career of the student of Jacob Fries, leader of the Burschenschaften, educational reformer, and professor of philosophy and law Karl Hermann Scheidler. It examines Scheidler's interventions into political and constitutional debates during the German Vormärz and argues that he developed a unique brand of liberal corporatism that has been overlooked or misunderstood by intellectual historians—one that attempts to bridge the gap between eighteenth-century natural law and nineteenth-century political nationalism by defending the corporate autonomy of the churches and universities, and by promoting a combination of public virtue and moral perfection that he dubbed "political Protestantism." It emphasizes Scheidler's polemical articles against the "Hegel school" and the "New Hegelians" in Rotteck's and Welcker's Staats-Lexikon . It proposes that a detailed examination of Scheidler's work provides a clearer understanding of how liberalism emerged as a distinct political ideology during the Vormärz and how one strand of German liberalism defined itself against Hegelianism.